Infosecurity 2008 threat analysis - Clark, Champ, III. (Burlington, MA : Syngress Pub., 2008)
An all-star cast of authors analyze the top IT security threats for 2008 as selected by the editors and readers of Infosecurity Magazine. This book, compiled from the Syngress Security Library, is an essential reference for any IT professional managing enterprise security. It serves as an early warning system, allowing readers to assess vulnerabilities, design protection schemes and plan for disaster recovery should an attack occur. Topics include Botnets, Cross Site Scripting Attacks, Social Engineering, Physical and Logical Convergence, Payment Card Industry (PCI) Data Security Standards (DSS), Voice over IP (VoIP), and Asterisk Hacking. Each threat is fully defined, likely vulnerabilities are identified, and detection and prevention strategies are considered. Wherever possible, real-world examples are used to illustrate the threats and tools for specific solutions. * Provides IT Security Professionals with a first look at likely new threats to their enterprise * Includes real-world examples of system intrusions and compromised data * Provides techniques and strategies to detect, prevent, and recover * Includes coverage of PCI, VoIP, XSS, Asterisk, Social Engineering, Botnets, and Convergence.
Botnets : a call to action -- Botnets overview -- Cross-site scripting fundamentals -- XSS theory -- XSS attack methods -- Protecting critical infrastructure : process control and SCADA -- Final thoughts -- Why PCI is important -- Protect cardholder data -- Understanding and taking advantage of VoIP protocols -- Asterisk hardware ninjutsu -- Social engineering.
Includes index.
Keywords: Database security; Computer security; Data protection; Computers -- Access control; Telecommunication -- Security measures; Database security. Computer security. Data protection. Computers -- Access control. Telecommunication -- Security measures; Electronic books